Implementasi Pendidikan Adab (Ta’dib) sebagai Upaya Pembentukan Insan Kamil di Jenjang Dasar - Asalin Musoffa Sa’ad; Zaeni Dahlan (AZKIA: Journal of Islamic Education in Asia, 2025)
This research addresses the critical need for character education (ta'dib) in the modern Indonesian educational context, which often prioritizes technological advancement over moral development. PADI Elementary School, which adopts a pesantren (Islamic boarding school) system, serves as a case study for implementing such values. This study aims to describe the implementation, obstacles, and solutions of character education (ta'dib) at PADI Elementary School in its effort to shape students into Insan Kamil (complete/perfect human beings). The research employs a qualitative approach, utilizing observation and interviews with the school principal and a fifth-grade homeroom teacher to collect data. The implementation of character education is conducted effectively through several methods: (1) Special subjects like "Syair Adab" (Poetry of Manners) and lessons from the kitab adab al-insan fii al-islam using bandongan and demonstration methods. (2) Habituation programs, notably the use of a "Muttaba'ah" book to monitor students' practice of obligatory worship (fardhu 'ain) and daily manners at home, facilitating crucial collaboration between school and parents. (3) The establishment of clear rules and disciplinary measures (Aturan dan Tata Adab). The main obstacles identified include some students violating basic manners (e.g., verbal fights, tardiness, not completing the Muttaba'ah book) and a lack of parental involvement in mentoring their children's habituation at home. Solutions are applied through a system of motivational rewards (e.g., praise, star system) and educational punishments (e.g., warnings, point deductions, discussion).